Pengaruh Target Keuangan, Transaksi Pihak Berelasi, dan Rangkap Jabatan terhadap Kecurangan Laporan Keuangan - Tri Lestari, Bunga; Reni Oktavia (Goodwood Akuntansi dan Auditing Reviu, 2024)
Purpose: This study aims to determine whether manufacturing companies in the consumer goods industry, classified as family businesses and listed on the Indonesia Stock Exchange, can detect financial statement fraud through financial targets, related-party transactions, and CEO dualism. Research Methodology: This study employed a quantitative approach. Based on the research criteria, the sample comprised of 11 companies. The data analysis included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Results: The findings indicate that managerial overlap and financial targets influence financial statement fraud. Conversely, related-party transactions do not influence financial statement fraud. Limitations: The variables in this study explain 42.8% of the variance in discretionary accruals, as indicated by a coefficient of determination of 0.428. The remaining 57.2% were attributed to other factors. Contribution: This study is expected to provide a deeper understanding of the potential for financial statement fraud. Therefore, management, owners, and other stakeholders should be better prepared to prevent fraud and enhance corporate resilience.